Destination--deep sea - Grupper, Jonathan (Washington, D.C. : National Geographic Society, 2000)
Describes the physical characteristics, behavior, and habitat of various sea creatures, from familiar crabs to giant whales to tube worms.
Keywords: Marine animals -- Juvenile literature; Marine animals